Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I got this problem:

Let $A \in M_n(\mathbb R)$ such that $A = -A^T$. Prove that $e^A$ is an orthogonal matrix.

I succeeded in showing that $e^{(A^T)}e^A=I$ but did not succeed in proving that $e^{(A^T)}=(e^A)^T$. Any suggestions? Thanks to helpers!

share|improve this question
    
Consider definition and formula : $e^A =\sum_{i=0}^\infty \frac{1}{i!}A^i$ and $(XY)^T = Y^TX^T$ –  Hee Kwon Lee Feb 11 at 10:58
    
I still have a problem. Could you explain more? –  Shlomi Feb 11 at 11:07
add comment

1 Answer

I will add details : $$ [e^A]^T = \bigg[\sum_{i=0}^\infty \frac{1}{i!}A^i \bigg]^T = \sum_{i=0 }^\infty \frac{1}{i!} (A^i)^T=\sum_{i=0 }^\infty \frac{1}{i!} (A^T)^i =e^{A^T} $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.